The impact of the HPV vaccine on the world: initial outcomes and challenges - Ribeiro, Daniel Vitorino; Steffens, Sérgio Murillo; Fedrizzi, Edison Natal (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Human papillomavirus (HPV) infection can be considered an epidemic in the world and in Brazil. This infection accounts for virtually all cases of cervical cancer, most malignant anal, vaginal and oropharyngeal tumors, and a large number of cases of cancer of the penis and vulva. The most effective way to prevent this infection is through vaccination. Several countries, including Brazil, have already introduced this vaccine into the public vaccination programs and are observing the real-life results of decreasing HPV-associated diseases. Objective: To evaluate the effectiveness of HPV vaccination in preventing virus-induced diseases in countries that have adopted it for a longer time, in a different scenario from clinical studies. Methods: This is a bibliographic review study in journal databases PubMed, LILACS, SciELO and Scopus, with publications dated from 2000 to 2019. The research was restricted to articles in English and Portuguese and studies conducted in humans. Ten studies that were considered relevant were selected. Furthermore, additional articles found by free search were selected. After this phase, the chosen publications were obtained in full for reassessment of their methodology and results. Results: The HPV vaccine demonstrated its effectiveness in reducing the incidence of HPV infection and/or anogenital warts and/or precancerous lesions in the seven countries analyzed by the study: Australia, Brazil, Denmark, United States of America, New Zealand, Czech Republic and Sweden. The impact was bigger in countries that introduced it earlier, such as Australia, where the vaccine virtually eliminated the incidence of genital warts in women aged under 21 years. Although Brazil implemented the vaccine a few years ago, a preliminary study was conducted in Campos dos Goytacazes, RJ, where the vaccine was implemented in 2010, showing a 55% reduction in the incidence of genital warts for women aged under 21 years old, between 2007 and 2012. Conclusion: The HPV vaccine is highly effective in protecting against HPV infection and disease in the countries where it has been implemented, with better results than those seen in clinical trials.